NILAI-NILAI PENDIDIKAN ISLAM DALAM KISAH ‘UZAIR (Analisis Kajian dalam Q.S. Al-Baqarah Ayat 259 dan Q.S. At-Taubah Ayat 30) - Dedek Dian Sari, Zulheddi, Edi Saputra (Pascasarjana UIN Sumatera Utara, 2019)
Abstrac: In this study, the author uses the methodology of library research with a qualitative approach. Thetechnique of collecting the data is carried out through analysis of the Qur’anic text through Qur’anic interpretations,namely the discussion of information in the Koran which in this case the primary source is the book of theKoran and the Qur’anic Interpretation Book and secondary sources are books related to Islamic educationand stories of the Qur’an. Prophets and Apostles. The aims of this study was to explore and examine thevalues of Islamic education in the stories of ‘Uzair Surat al-Baqarah verse 258 and at-Taubah verse30. The results of this study are 3 (three) values of Islamic education, including the values of aqeedah orcreed, intellectual, and morals. All of these values are relevant to current education. Aqeedah will educatepeople to unleash God and not associate with Him and believe in His prophets and apostles, intellectualswill educate people to use their minds in thinking about natural phenomena, morals will make humanshave adab in social relations between humans and the environment .Key Words: Value, Islamic studies, Relevance.